Environmental Radiotoxical Dosimetry of Soil Samples of Selected Locations in Federal College of Education (Technical) Gusau Zamfar State - Ukiri, Moses; Kutigi, Idris; Bappah, Hawal H. (FUDMA Journal of Renewable and Atomic Energy, 2026)
Naturally occurring radioactive materials (NORMs) in soils constitute an important source of environmental radiation exposure and may pose potential health risks to populations occupying affected environments. This study presents a baseline radiological assessment of soils within the Federal College of Education (Technical), Gusau, Zamfara State, Nigeria, providing essential reference data for future environmental monitoring and radiation protection in an institutional setting. Twenty soil samples were collected from strategically selected locations across the campus and analyzed using gamma-ray spectrometry with a NaI(Tl) detector to determine the activity concentrations of 40K,226Ra, and 232Th, as well as associated radiological hazard indices. The mean activity concentrations of 40K, 226Ra, and 232Th were 390.09, 22.68, and 30.29 Bq kg⁻¹, respectively. These values are below the corresponding global average values reported by UNSCEAR, indicating low natural radioactivity within the study area. Radiological hazard assessment showed mean values of 95.67 Bq kg⁻¹ for radium equivalent activity (Raeq), 44.41 nGy h⁻¹ for absorbed dose rate, 0.258 for the external hazard index (Hex), and 0.319 for the internal hazard index (Hin). The average annual effective dose equivalents were 0.222 mSv y⁻¹ for indoor exposure and 0.055 mSv y⁻¹ for outdoor exposure. Excess lifetime cancer risk values remained within internationally accepted safety limits. The measured radiological parameters were generally lower than the recommended thresholds established by the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR), the Organisation for Economic Co-operation and Development (OECD), and the International Commission on Radiological Protection (ICRP). These findings indicate that the soils within the study area do not present significant radiological health concerns. The study establishes a valuable baseline radiological database for educational institutions in Zamfara State and contributes to ongoing environmental radiation surveillance in regions influenced by diverse geological and anthropogenic activities.